Sarbanes-Oxley and Its Impacts on Mergers and Acquisitions - Kannan, M.K. (2007)
The aim of the present study is to conceptually integrate insights from the Sarbanes-Oxley Act to the research area of impacts on mergers and acquisitions (M&A) aftermath of enactment of the Act. The primary theories of Sarbanes-Oxley are understood in detail.